Crystallization in arylate polyesters to periodically ringed assembly. Issue 2 (12th September 2018) - Woo, Eamor M.; Lee, Ming‐Syuan
Abstract : Crystallization of arylate polymers are reviewed and analyzed for proposing interpretations for mechanisms of interior and surface‐relief lamellae packed into periodic banded patterns. Ring bands in polymers are typically characterized with dramatically different types that are distinguished by shapes, patterns, birefringence distribution, and height variation in ridge‐valley regions. Interior lamellae versus surface crystals that assemble into ring bands of different types are interpreted using novel mechanisms to be exemplified in this review. As the surface topology differs among different polymers with banding patterns, the inner structures may also differ correspondingly. In the past half a century, most investigations had approached the issues of periodic banding phenomenon only from top‐surface views on thin‐film specimens, which had encountered dilemma in incompleteness of searching for valid mechanisms. The surface relief and interior crystals in correlating with periodically optical birefringence in crystallized arylate polyesters are surveyed. Via thorough probes into the interior lamellar assembly that correlates with the optical birefringence in ringed spherulites of a series of arylate polyesters, objectives were to more fully expound plausible mechanisms, and aimed to identify common traits and features of banded polymer spherulites in homologous series of aryl‐polyesters. Abstract : The correlation of surface‐relief morphology and interior lamellae assembly with periodically optical birefringence in crystallized spherulites is surveyed on a series of arylate polyesters. The objective of this Review is to illustrate novel mechanisms aiming to identify traits and features of banded polymer spherulites.